The effect of emotional motivation on strategy flexibility: the moderating role of task load - Wang, Yun; Zhu, Chuanlin; Zuo, Dan; Liu, Jingyi; Liu, Dianzhi (Frontiers in Psychology, 2023)
This study investigated the effect of emotional motivation on the flexibility of strategy utilization under different levels of task workload. Using two-digit multiplication estimation as an example, an emotional priming paradigm and strategy-conversion task were employed. Participants were asked to complete two-digit multiplication computational estimation using different strategies, under different emotional motivational priming conditions. The results revealed that the switch costs under low intensity priming were significantly lower than those under high intensity priming under high workload, while the switch costs under avoidance direction priming were significantly lower than those under approach direction priming under low workload. This study demonstrated that high workload could bring about a low intensity advantage, while low workload could induce an avoidance direction advantage, suggesting that task load could moderate the impact of emotional motivation on arithmetic strategy utilization flexibility, and avoidance motivation is not always detrimental to cognitive flexibility.